Analisis Kelayakan Investasi Mesin Pembangkit Listrik Di PT Sungai Bahar Pasifik Utama - Devi Lastina; Achmad Alfian (Universitas Katolik Musi Charitas, 2019)
Investment feasibility analysis is a study conducted on a project (usually an investment project) whether it can be implemented or not to achieve success. Research was conducted in PT Sungai Bahar Pasifik Utama, Muaro Jambi, Jambi Province to determine the electrical energy generated from the rest of processing fiber and shell of palm to transmit the energy to a housing around the location factory. On this research will increase the engine power plant costs Rp 13.400.000.000 with economical life of 10 years and then analyzed using the analysis of feasibility of investment by 4 of investment valuation (Payback Period, Net Present Value, Profitability Index and Break Even Point analysis). As for the results of the value is from Payback Period criterion `of 96.27 months or 8,02 years, NPV equal to Rp 1,032,376,973, magnitude of PI is 1.077, and The calculation result of Break Even Point is the result 128.933 houses which must be received by PT SBPU amounting to Rp 18,356,164,384. Thus, the investment of electricity generation machine feasible to be implemented because it meets the requirements of economic feasibility.